US Policy in Afghanistan and Iraq : Lessons and Legacies - Edited by Brown, Seyom and Scales, Robert H. (New Dehli Viva Books, 2017)
How have the costs, both human and material, of US involvement in the conflicts in Afghanistan and Iraq affected the country's will for conducting regime-change operations? What are the implications for issues of strategy? The authors of US Policy in Afghanistan and Iraq assess the impact of the two conflicts on US foreign policy, military planning, and capacities for counterinsurgency and state building. They also offer keenly insightful guidance for avoiding the pitfalls and increasing the prospects for success when the United States does intervene. -- Publisher description.
Include Bibliography and Index
Keywords: Military planning -- United States -- United States